P687 Prevalence of iron deficiency and anaemia in the outpatient Inflammatory Bowel Disease population: a Dutch national cross-sectional study. (21st January 2022) - Loveikyte, R; Boer, M; van der Meulen, C N; ter Steege, R W F; Tack, G; Kuyvenhoven, J; Jharap, B; Vu, M K; Vogelaar, L; West, R L; van der Marel, S; Römkens, T; et al.
Abstract: Background: Iron deficiency (ID) and anaemia in Inflammatory Bowel Disease (IBD) are associated with reduced quality of life, worse disease outcomes, and an increase in healthcare costs. In the European guidelines, anaemia is listed as one of the treatment goals. The data on the prevalence of anaemia and ID are inconsistent. Therefore, we evaluated the prevalence of ID, anaemia, and potential risk factors in a large Dutch outpatient population. Methods: Between January and November 2021, consecutive adult outpatients with IBD, who did not have significant comorbidities associated with anaemia, were included in this study across 16 general, teaching, and academic hospitals within the Netherlands. Besides demographic and clinical data, relevant biochemical parameters such as haemoglobin (Hb), Mean Corpuscular Volume (MCV), iron indices, and inflammatory markers (e.g., C-reactive protein (CRP) and faecal calprotectin (FCP)) were extracted from medical records. Active IBD was defined by either CRP >5mg/L or FCP >150mg/g. ID was defined by ferritin <100µg/L in case of inflammation and <30µg/L in quiescent IBD, or transferrin saturation <20%. The Dutch national reference range was used to define anaemia: Hb <7.5mmol/L or <8.5mmol/L for females and males, respectively. The data were analysed by stratifying patients into Crohn's Disease (CD) and Ulcerative Colitis (UC) groups, with the latter also including patients with IBD-unclassified (IBDU). Results: In total, 2197 patients (1271 CD, 849 UC, and 77 IBDU) were included in the study. The overall prevalence of anaemia, iron-deficiency anaemia (IDA), and ID was: 18.0%, 12.2%, and 43.4%, respectively. The prevalence of all three conditions did not differ between the CD and UC groups ( P >0.05). Severe anaemia (Hb<6.2 mmol/L) was observed only in 28 patients. ID was more frequently observed in biochemically active IBD compared with quiescent IBD (70.8% versus 23.9%; P <0.001). Female gender, younger age, low MCV, and a twofold increase in biochemical inflammation were associated with ID development in multivariable analysis: Log2 FCP [OR 1.39; 95% CI: 1.29–1.50; P <0.001] and Log2 platelets [OR 1.85; 95% CI: 1.16–2.95; P <0.01]. In multivariable analysis, low ferritin and MCV, inflammation, older age, and male gender were associated with a higher risk of anaemia; however, disease location or behaviour did not affect the risk of developing anaemia or ID. Conclusion: One in five ambulatory IBD patients presents with anaemia that is primarily caused by ID. Inflammation increases the risk of ID and anaemia regardless of IBD type or disease location. High ID prevalence suggests the need for screening and treatment optimisation.